Good girls go to heaven; bad girls... learn to be good : critical discourse analysis of quizzes in teenage girl's magazines - Ostermann, Ana Cristina (1995)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão